Dual‐Responsive SPMA‐Modified Polymer Photonic Crystals and Their Dynamic Display Patterns. Issue 20 (28th May 2018) - Gao, Zewen; Gao, Dongsheng; Huang, Chao; Zhang, Hanbing; Guo, Jinbao; Wei, Jie
Abstract: Light and electrothermal responsive polymer photonic crystals (PCs) modified with 1′‐acryloyl chloride‐3′, 3′‐dimethyl‐6‐nitro‐spiro(2 H ‐1‐benzopyran‐2, 2′‐indoline) (SPMA) are proposed, and their dynamic display patterns are achieved through the combination of the SPMA‐modified PCs and a patterned graphite layer. These PCs exhibit fluorescence under UV light irradiation because of the isomerization of the SPMA, which is restricted in the shell of the polymer colloidal spheres. After a voltage is applied to the patterned graphite layer, the fluorescence of PCs in the specific area disappears, and dynamic display patterns are obtained. Under UV light irradiation, the PCs change from the "partial‐fluorescence" state to the initial "fluorescence" state, and the patterns disappear. Using this technique, the PC pattern "M L N" on the glass substrate and PC patterns from "0" to "9" on the paper substrate are fabricated. Thus, these dual‐responsive PCs have potential applications in information recording, anticounterfeiting, dynamic display, and photoelectric devices. Abstract : 1′‐Acryloyl chloride‐3′, 3′‐dimethyl‐6‐nitro‐spiro(2 H ‐1‐benzopyran‐2, 2′‐indoline) (SPMA)‐modified photonic crystals (PCs) with light and electrothermal response and their dynamic display patterns are prepared. With UV irradiation, the PCs exhibit fluorescence due to the isomerization of PS@P(MMA‐ co ‐SPMA). After a voltage is applied, increasing temperature of the graphite layer causes the disappearance of fluorescence. Thus, the PC patterns "M L N" and "0" to "9" on different substrates are fabricated.